2020
DOI: 10.21203/rs.3.rs-26916/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between five types of Tumor Necrosis Factor-α Gene Polymorphism and Hepatocellular Carcinoma Risk: A Meta-Analysis

Abstract: Background: Research focusing on the relationship between five types of tumor necrosis factor-alpha (TNF-α) SNPs and the risk of hepatocellular carcinoma (HCC) were still controversial. Hereby, we performed a meta-analysis to determine the association between TNF-α promoter SNPs: -1031 T/C, -863 C/A, -857 C/T, -308 G/A, and -238 G/A with HCC risk. Methods: We interrogated articles from journal database: PubMed, Pro-Quest, EBSCO, Science Direct, and Springer to determine the relationship between five types of S… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Research has indicated that signal nucleotide polymorphisms (SNPs) in the TNF-α gene, including −863 C/A, −857 C/T, −308 G/A, and −238 G/A, are linked to the risk of developing HCC. These SNPs located on the TNF-α promoter can influence the level of TNF-α expression and lead to increased and continuous TNF-α production and are associated with a heightened HCC risk [23]. A substantial correlation was observed between the TNF-a GG genotype, and the occurrence of HCC [21].…”
Section: Chronic Inflammationmentioning
confidence: 99%
“…Research has indicated that signal nucleotide polymorphisms (SNPs) in the TNF-α gene, including −863 C/A, −857 C/T, −308 G/A, and −238 G/A, are linked to the risk of developing HCC. These SNPs located on the TNF-α promoter can influence the level of TNF-α expression and lead to increased and continuous TNF-α production and are associated with a heightened HCC risk [23]. A substantial correlation was observed between the TNF-a GG genotype, and the occurrence of HCC [21].…”
Section: Chronic Inflammationmentioning
confidence: 99%
“…Similarly, functional studies have revealed that the G allele of the SNP variant −764G/C, situated nearby the IFN-γ promoter region, enhances promoter activity by a factor of two to three fold, correlating with both viral clearance and better treatment response in individuals with HCV infection [32]. In the context of malignancies, TNFα SNP (−863C/A, −857 C/T, −308 G/A, and −238 G/A) was strongly associated with a higher risk of hepatocellular carcinoma (HCC) [33], and the different combinations of SNPs of TNFα (−238G/A or −308G/A) with IL-10 (−592 C/A) were highly prevalent among patients with cervical cancer. PBMC (samples from patients with cervical cancer) activated with PHA also indicated that the TNFα (−308A/A) genotype demonstrated increased proliferation rates, elevated IL-4 and TGF-β, and decreased IL-2 levels [34], and it was postulated that SNPs of cytokine genes act as the potential predictors of cervical HPV infection progression to neoplasia.…”
Section: Introductionmentioning
confidence: 99%
“…In inheritance model analysis, the A/C-A/A genotype was related to a reduced risk of cervical cancer (P = 0.006, OR = 0.77; 95% CI = 0.64-0.93) in the dominant model. Previous studies have shown that rs1800630 is associated with gastric cancer and hepatocellular carcinoma [44,45], with the A allele of rs1800630 being a protective factor in the former but a risk factor in the latter. Our results show that the A allele of rs1800630 is a protective factor against cervical cancer (OR = 0.827; 95% CI = 0.715-0.959).…”
mentioning
confidence: 98%